Students, faculty perceptions and effectiveness of the early introduction of clinical skills teaching in the medical curriculum - Mahmoud S. Khalil, PhD, MD; Nouf Alrumaihi, MD; Jude Feda, MD; Lulu Alnuaim, MD; Hamza Abdulghani, MD; Khalid Fouda, PhD, MD; Saleh AlDahri, MD; Mona Soliman, PhD, MD (Journal of Taibah University Medical Sciences, 2023)
الملخص: أهداف البحث: يساعد الإدخال المبكر للمهارات السريرية الطلاب على تطوير المهارات السريرية وتطبيقها بشكل مناسب خلال السنوات السريرية. من المهم تقييم تصورات طلاب الطب وأعضاء هيئة التدريس فيما يتعلق بالإدخال المبكر لتدريس المهارات السريرية وفعاليتها. طريقة البحث: تم تصميم منهج المهارات السريرية بالتكامل مع المنهج القائم على حل المشكلات في العامين الاول و الثاني في كلية الطب ، جامعة الملك سعود ، من يناير 2019 إلى ديسمبر 2019. تم تصميم استبانة الطلاب وأعضاء هيئة التدريس. تم تقييم تأثير فعالية تدريس المهارات السريرية من خلال مقارنة نتائج الاختبارات السريرية المبنية موضوعيا لطلاب السنة الثالثة الذين تلقوا جلسات المهارات السريرية المبكرة مع أولئك الذين لم يفعلوا ذلك. بلغ إجمالي عدد الطلاب المستجيبين 461/598 ، منهم 259 (56.2٪) من الذكور و 202 (43.8٪) من الإناث. كانت الاستجابات في السنة الأولى 247 (53.6٪) والثانية 214 (46.4٪). بلغ عدد أعضاء هيئة التدريس المستجبين 35/43. النتائج: كان غالبية الطلاب وأعضاء هيئة التدريس لديهم رضا عن أن الإدخال المبكر للمهارات السريرية أدى إلى زيادة ثقة الطلاب عند التعامل مع مرضى حقيقيين، ومنح الفرصة لإتقان المهارات، وتعزيز المعرفة النظرية والمهارات السريرية، والتعلم المحفز، وزيادة حماس الطلاب ليصبحوا أطباء. قام طلاب السنة الثالثة الذين درسوا المهارات السريرية في العامين الأكاديميين الأول والثاني خلال عامي 2017-2018 و 2018-2019 بزيادة كبيرة في متوسط الدرجات في الاختبارات السريرية المبنية موضوعيا خلال دوراتهم في منهج الجراحة (32.6 و 37.4 للإناث ؛ 35.2 و 35.7 للذكور) وفي منهج الطب (31.2 و 34.1 للإناث ؛ 34.3 و 37.7 للذكور) على التوالي مقارنة بالطلاب الذين لم يدرسوا المهارات السريرية خلال العام الدراسي 2016-2017 في منهج الجراحة ، (22.2 و 23.2 )؛ وفي الطب ( 25.1 و 24.2) للإناث والذكور على التوالي. الاستنتاجات: كان التعرض المبكر لطلاب الطب للمهارات السريرية تدخلا إيجابيا يسد الفجوة بين العلوم الأساسية والممارسة السريرية. Abstract: Objective: We hypothesized that the early introduction of clinical skills (CS) would help students to develop and apply clinical skills appropriately during the clinical years. Evaluating the perceptions of medical students and faculty regarding the early introduction of CS teaching and its effectiveness are important. Methods: The CS curriculum was designed by integration with the system-oriented problem-based curriculum in years 1 and 2 at the College of Medicine, KSU, from January 2019 to December 2019. Students and faculty questionnaires were also designed. The impact of CS teaching effectiveness was assessed by comparing OSCE results for year-3 students who received early CS sessions with those who did not. The total number of student respondents was 461/598; and 259 (56.2%) were male and 202 (43.8%) were female. The first- and second-year respondents were 247 (53.6%) and 214 (46.4%), respectively. The number of faculty respondents was 35/43. Results: The majority of students and faculty were satisfied that the early introduction of CS increased student confidence when dealing with real patients, provided the opportunity to master skills, consolidated theoretical knowledge and clinical skills, motivated learning, and increased the enthusiasm of students to become doctors. The third-year students who received CS teaching in years 1 and 2 (during 2017–2018 and 2018–2019) showed a significant increase in mean grades (p value; 0.00) in OSCE tests during their courses in surgery (from 32.6 to 37.4 for females; 35.2 to 35.7 for males) and medicine (31.2–34.1 for females; 34.3 to 37.7 for males), respectively, when compared to students who did not receive CS teaching during the academic year 2016–2017 (in surgery, 22.2 and 23.2; in medicine 25.1 and 24.2) for females and males respectively. Conclusion: Early exposure of medical students to CS is a positive intervention that bridges the gap between basic sciences and clinical practice.